Pakistan’s cotton and textile economy: Intersectoral linkages and effects on rural and urban poverty - Cororaton, Caesar B.; Orden, David (International Food Policy Research Institute, 2008)
Pakistan’s economy relies heavily on its cotton and textile sectors. The cotton-processing and textile industries make up almost half of the country’s manufacturing base, while cotton is Pakistan’s principal industrial crop, supplying critical income to rural households. Altogether, the cotton-textile sectors account for 11 percent of GDP and 60 percent of export receipts. The future of this vital component of the national economy is uncertain, however. These industries face the challenges of unstable world prices and increased competition resulting from global liberalization of the multilateral textile and clothing trade. At the same time, Pakistan’s macroeconomic situation is volatile. Given such challenges and volatility, this study investigates what the future might hold for Pakistan’s cotton and textile industries and its implications for rural and urban poverty reduction in the country. The study uses a computable general equilibrium (CGE) model calibrated to a 2001–02 social accounting matrix of the Pakistan economy to conduct experimental simulations of possible economic changes. The CGE model results are linked to the nation-wide 2001–02 Pakistan Household Integrated Economic Survey to examine the implications the simulated developments have for Pakistani poverty. Simulation 1 examines the effects of a doubling of foreign capital inflows, as occurred from 2002 to 2006, before a subsequent financial crisis emerged in 2008. Simulation 2 analyzes the counterfactual effects of an increase in world prices of cotton lint and yarn and/or textiles which would have offset declines experienced in the late 1990s and early 2000s. Pakistan’s strong textile association motivates Simulation 3, which examines the effects of a 5-percent increase in government production subsidies to the industry. Simulation 4 uses a dynamic-recursive version of the model to analyze the short- and long-run effects of a 5-percent increase of total factor productivity (TFP) in cotton, lint and yarn, and textile production.